Chylous ascites as a manifestation of child abuse: a case report - Granados González, José Luis; Cura Esquivel, Idalia Aracely; García Calderín, Diego de Jesús; Uribe González, Nydia Tatiana (Masson Doyma México, S.A, 2009)
Chylous ascites is a rare pathology. It can be primary due to congenital defects or secondary to obstruction, trauma or neoplasia. We present an infant patient with chylous ascites due to damage to the cisterna chyli caused by traumatic lumbar vertebral fractures due to child abuse. Treatment of chylous ascitis has three objectives: improve and maintain the patient’s nutritional status, decrease the production of chyle, and correct the cause. Initial treatment is conservative in pediatrics. Up to 10% of cases are caused by child abuse and occurs in all social groups. Healthcare professionals should be alert to its presence to make an early diagnosis and an opportune intervention.